Medicinal Plants of the Bhagirathi Valley Lying in the Uttarkashi Forest Division of Uttar Pradesh - Unival, M. R. (Indian Forester, 1968)
During a preliminary survey of Bhagirathi valley in the Himalayas, sixty-one medicinal plants belonging to thirty-seven families were collected and the same have been listed and described here. They are either commercially or traditionally important in medicine. The information accompanying each drug plant of the list Is based on field data collected from local drug collectors, drug markets and Vaidyas with especial reference to the parts used, localities from. Where they are collected, local and Sanskrit names and the uses made of them especially in folk medicine.